2014
DOI: 10.1371/journal.pmed.1001610
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Viral Introductions in Sustaining Community-Based HIV Epidemics in Rural Uganda: Evidence from Spatial Clustering, Phylogenetics, and Egocentric Transmission Models

Abstract: Using different approaches to investigate HIV transmission patterns, Justin Lessler and colleagues find that extra-community HIV introductions are frequent and likely play a role in sustaining the epidemic in the Rakai community. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
150
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(158 citation statements)
references
References 35 publications
7
150
0
1
Order By: Relevance
“…[17][18][19] Datasets (1) and (2) contained viral sequences spanning a 325-330 base pair segments of the HIV gp41 gene, generated using the Roche 454 method. 17,18 Dataset (1) comprised of nine epidemiologically linked couples with prior evidence of a virally linked transmission event (donor and recipient).…”
Section: Hiv-1 Sequence Datasetsmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19] Datasets (1) and (2) contained viral sequences spanning a 325-330 base pair segments of the HIV gp41 gene, generated using the Roche 454 method. 17,18 Dataset (1) comprised of nine epidemiologically linked couples with prior evidence of a virally linked transmission event (donor and recipient).…”
Section: Hiv-1 Sequence Datasetsmentioning
confidence: 99%
“…19 Consensus sequences were obtained using Sanger sequencing (gp41 fragment, HXB2 nt 7858 to 8260) as previously described. 20 Of the 1,022 individuals, 182 individuals were identified to be part of an epidemiologically linked heterosexual couple (91 couples), where either one or both partners named the other as a sexual partner.…”
Section: Hiv-1 Sequence Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,7,[11][12][13][14][15]20 While HIV clustering patterns have been well characterized among men who have sex with men (MSM), [7][8][9][10][11][13][14][15][16][17][18][19][20][21][22] the structure and dynamics of heterosexual HIV transmission networks in sub-Saharan Africa are understudied. 12,[23][24][25][26][27] High sampling density in local communities has been associated with a higher extent of HIV clustering. 23 Studies with low sampling density showed minimal HIV clustering.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of growth curve has three qualitative phases: exponential growth, linear growth, and a slow final phase when the susceptible population is almost depleted. The waiting times until the next transmission, which determine the coalescence times in the tree, are MSM/USA (Little et al 2014) MSM/Taiwan (Kao et al 2011) MSM/Beijing (Wang et al 2015) HET/Uganda (Grabowski et al 2014) HET/Malawi (McCormack et al 2002) HET/Botswana (Novitsky et al 2013(Novitsky et al & 2014 IDU/Romania (Niculescu et al 2015) IDU/Estonia (Zetterberg et al 2004) dependent on the growth phase of the epidemic. Therefore, we hypothesize that it is the growth phase at the time of sampling which most affects tree shape, rather than the specific values of I or N ( Supplementary Fig.…”
Section: Analysis Of Ba Model With Synthetic Datamentioning
confidence: 99%